2023
DOI: 10.1093/plphys/kiad423
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor VvWRKY70 inhibits both norisoprenoid and flavonol biosynthesis in grape

Abstract: Norisoprenoids and flavonols are important secondary metabolites in grape berries (Vitis vinifera L.). The former is a class of ubiquitous flavor and fragrance compounds produced by the cleavage of carotenoids, and the latter, which is derived from the flavonoid metabolic pathway, has been proposed as a general quality marker for red grapes. However, the transcriptional regulatory mechanisms underlying norisoprenoid and flavonol production are still not fully understood. In this study, we characterized a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For the gene overexpression experiment, ‘Cabernet Sauvignon’ calli were obtained following our previous reports [ 54 , 55 ]. The calli underwent culture on B5 solid medium, equipped with 3.21 g/L B5 basic medium, 30 g/L sucrose, 2.5 g/L acid-hydrolyzed casein, 0.2 mg/L kinetin, 0.1 mg/L 1-naphthyl acetic acid, and 3.0 g/L plant gel at pH 5.8 6.0 and kept in the dark at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the gene overexpression experiment, ‘Cabernet Sauvignon’ calli were obtained following our previous reports [ 54 , 55 ]. The calli underwent culture on B5 solid medium, equipped with 3.21 g/L B5 basic medium, 30 g/L sucrose, 2.5 g/L acid-hydrolyzed casein, 0.2 mg/L kinetin, 0.1 mg/L 1-naphthyl acetic acid, and 3.0 g/L plant gel at pH 5.8 6.0 and kept in the dark at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…Table S5 (see online supplementary material) displays the primers used in the process, while further details can be found in Wei et al. ’s previous publication [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of VqWRKY31 from Vitis quinquangularis in grape increased accumulation of flavonoids and stilbenes and promoted expression of VvCHS , VvCHI , VvDFR , VvFLS , and VvSTS (stilbene synthase), which enhanced powdery mildew resistance [ 79 ]. Moreover, VvWRKY70 was identified as a transcriptional repressor of flavonol biosynthesis in grape by inhibiting the transcriptional activity of VvFLS4 and VvCHS2/3 [ 80 ]. Overexpression of VvWRKY70 caused a reduction of flavonol contents in transgenic grape calli [ 80 ].…”
Section: Direct Transcriptional Regulation Of Flavonol Biosynthesismentioning
confidence: 99%
“…Moreover, VvWRKY70 was identified as a transcriptional repressor of flavonol biosynthesis in grape by inhibiting the transcriptional activity of VvFLS4 and VvCHS2/3 [ 80 ]. Overexpression of VvWRKY70 caused a reduction of flavonol contents in transgenic grape calli [ 80 ]. These WRKY TFs can directly regulate expression of FLS genes to participate in regulation of flavonol biosynthesis.…”
Section: Direct Transcriptional Regulation Of Flavonol Biosynthesismentioning
confidence: 99%
“…Confirmed by transgenic grape suspension cells, VvNAC17 is an activator of both PA and anthocyanin pathways ( Badim et al., 2022 ). Recently, Wei et al. (2023) found that VvWRKY70 is a bi-functional transcription factor that simultaneously represses norisoprenoid and flavonoid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%